Bifidobacterium and enteral feeding in preterm infants: Cluster‐randomized trial. Issue 5 (17th June 2014) - Totsu, Satsuki; Yamasaki, Chika; Terahara, Masaki; Uchiyama, Atsushi; Kusuda, Satoshi; Probiotics Study Group in Japan
Abstract Background This study evaluated the benefit of Bifidobacterium bifidum OLB6378 (B. bifidum) in very low‐birthweight (VLBW) infants (birthweight <1500 g) for the acceleration of enteral feeding. Methods A cluster‐randomized, double‐blind, placebo‐controlled trial was conducted in 19 hospitals, divided into two groups: the B group (n = 10 hospitals; B. bifidum given to infants within 48 h of birth) and the P group (n = 9 hospitals; infants received a placebo). The primary outcome was establishment of enteral feeding after birth, defined as the postnatal day at which enteral feeding exceeded 100 mL/(kg/day). Secondary outcomes were defined as incidence of morbidity and somatic growth before discharge. Results Overall, 283 VLBW infants were enrolled in the study: B group, n = 153; and P group, n = 130. Enteral feeding was established within 21 days after birth in 233 infants, of whom 119 received B. bifidum and 114 received placebo until their bodyweight reached 2000 g. Enteral feeding was established significantly earlier in the B group, at 11.0 ± 3.6 days versus 12.1 ± 3.8days in P group (P < 0.05). Infant growth during the stay in the neonatal intensive care unit was not different between groups, but the incidence of late‐onset sepsis among all enrolled infants was significantly lower in the B group (3.9%, 6/153) than in the P group (10.0%, 13/130; P < 0.05). No differences were observed in the incidence of other adverse outcomes including mortality. Conclusions B. bifidum in VLBW infants accelerated the establishment of enteral feeding after birth without increasing the incidence of adverse effects.